Adding Some Context: The Systemic Constraints on Coercion. (February 2013) - Rich, Jason
The literature has long been searching for the keys to understanding great power coercion. Currently, that literature has focused too narrowly on the coercive demand, failing to recognise that it is actually the end result of a systemically influenced process. This article calls attention to how polarity structures the perceptions and calculations of states. Ultimately, this impacts a sender's ability to project a clear, consistent demand and potent ultimatum as well as the target's calculations for compliance. Thus, if the literature wants to understand fully great power coercion, it is necessary to infuse the systemic context into the discussion.